Warrior churchmen of medieval England, 1000-1250 theory and reality - Nakashian, Craig M. (The Boydell Press, 2023)
Christianity has had a problematic relationship with warfare throughout its history, with the middle ages being no exception. While warfare came to be accepted as a necessary activity for laymen, clerics were largely excluded from military activity. Those who participated in war risked falling foul of a number of accepted canons of the church as well as the opinions of their peers. However, many continued to involve themselves in war - including active participation on battlefields. This book, focusing on a number of individual English clerics between 1000 and 1250, seeks to untangle the cultural debate surrounding this military behavior
Previously issued in print: 2016. - Includes bibliographical references and index
Keywords: Military religious orders; Monks / England / History / To 1500; Clergy / England / History / To 1500; England / History, Military